Kansas Field Research 2025 (Kansas Agricultural Experiment Station Research Reports, 2025)
Summary of research conducted in 2024-2025 on field production and management practices for crops in Kansas. Published in 2025 from the Kansas State University Agricultural Experiment Station and Cooperative Extension Service.
Keywords: corn; soybean; wheat; grain sorghum; weed control; fertilizer; planting dates; seeding rate; sustainable intensification; defoliation